Preparation method of electrochemically activated kaolin-based SAPO-34 molecular sieve and application thereof in methanol to olefins reaction

CN122977400APending Publication Date: 2026-10-27NANNING JINFENG NEW MATERIAL TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611195075.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-07
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

该方法能耗高,且活化程度难以精确控制:温度过低则晶格破坏不完全,温度过高则形成惰性尖晶石相

Benefits of technology

本发明提供了一种电化学活化高岭土基SAPO-34分子筛的制备方法,

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application discloses a preparation method of electrochemically activated kaolin-based SAPO-34 molecular sieves and application of the electrochemically activated kaolin-based SAPO-34 molecular sieves in a methanol-to-olefin reaction, and belongs to the technical field of molecular sieve catalyst preparation. The method strips a layered structure of kaolin through electrochemical anodic oxidation, forms ultrathin nanosheets, and generates active Si-Al sites. The release rate of Si is accurately controlled by using a pulse potential program, so that dynamic matching with SAPO-34 crystallization kinetics is realized. The electrochemically activated kaolin-based SAPO-34 molecular sieves with high crystallinity are prepared through electrochemical induction crystallization. The obtained catalyst has a three-stage continuous pore channel structure of micropores-mesopores-macropores, and exhibits high diene selectivity, low carbon deposition rate and long catalytic life in the methanol-to-olefin reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of molecular sieve catalyst preparation technology, specifically relating to a method for preparing an electrochemically activated kaolin-based SAPO-34 molecular sieve and its application in the methanol-to-olefins reaction. Background Technology

[0002] SAPO-34 molecular sieves possess a CHA topology and a pore size of approximately 0.38 nm, exhibiting excellent selectivity for low-carbon olefins in the methanol-to-olefins (MTO) reaction. However, the micropores of pure SAPO-34 are prone to carbon buildup and blockage, and its low mechanical strength makes it difficult to meet the requirements of fluidized bed processes. Kaolin, as a natural layered aluminosilicate, is widely available and inexpensive, making it an ideal catalyst support and silicon-aluminum source. However, kaolin has a stable crystal structure and low reactivity. When used directly as a silicon source, it suffers from slow Si release and a mismatch with the crystallization kinetics of SAPO-34, easily leading to the formation of Si-deficient regions within the crystal and the generation of AlPO4 or SAPO-18 impurity phases, thus reducing catalytic activity.

[0003] In the existing technology, the preparation of kaolin-based SAPO-34 catalyst mainly adopts the method of high-temperature calcination activation (700-900℃) combined with hydrothermal crystallization. This method has high energy consumption and the degree of activation is difficult to control precisely: if the temperature is too low, the lattice destruction is incomplete, and if the temperature is too high, an inert spinel phase is formed. In addition, the release rate of Si in kaolin is difficult to match with the consumption rate of SAPO-34 crystallization, resulting in uneven crystallinity and acidity distribution of the product. (2) The silicon source is added at once, and the concentration decays rapidly, which is not matched with the crystallization consumption rate. It is easy to form a Si-deficient region, generate AlPO4 or SAPO-18 impurity phase, and reduce the effective acid density; (3) The crystallization temperature is high (180-220℃), the nucleation rate and growth rate are unbalanced, the grain size is difficult to control, and large crystals of 0.5-2μm are usually obtained. The diffusion path is long, the carbon deposition rate is >10wt% / 100h, and the catalytic life is <100h.

[0004] Therefore, there is an urgent need to develop a novel preparation method that can efficiently activate kaolinite under mild conditions and precisely control the Si release kinetics. Summary of the Invention

[0005] To address the shortcomings of existing technologies, the present invention aims to provide a kaolin-reinforced rubber composite material for tire treads, which imparts electromagnetic responsiveness to kaolin through magnetic functionalization and dielectric modification, and utilizes a magnetic field-electric field synergistic external field to achieve radial orientation of the sheets.

[0006] The second objective of this invention is to provide a method for preparing the above-mentioned composite material, which achieves precise control of the orientation degree of kaolin sheets by optimizing the vulcanization process parameters.

[0007] One of the objectives of this invention is achieved through the following technical solution: A method for preparing an electrochemically activated kaolin-based SAPO-34 molecular sieve, comprising the following steps: S1. Electrochemical anodic oxidation exfoliation: Kaolin powder is pressed into electrode sheets as the anode, and anodic oxidation is performed for 30-120 min at a constant current density of 10-50 mA / cm² using 0.5-2 M NaOH or KOH solution as the electrolyte. During the anodic oxidation process, the Al-O octahedral layers between the kaolin sheets undergo selective dissolution, and the layered structure is exfoliated to form ultrathin kaolin nanosheets with a thickness of 5-20 nm and a radial dimension of 200-800 nm. At the same time, abundant ≡Si-O⁻ and ≡Al-O⁻ active sites are generated on the surface. S2. Pulse Potential Controlled Silicon Release: The kaolin nanosheets treated in step S1 are transferred to a crystallization reactor, and deionized water, phosphorus source, and template agent are added. A three-electrode system is used, in which the kaolin nanosheets are the working electrode, Pt is the counter electrode, and Ag / AgCl is the reference electrode. The release of Si is controlled by a pulse potential program: a reduction potential of -0.8 to -1.2V (vs. Ag / AgCl) is first applied for 60-120s to promote the breaking of Si-O bonds on the surface and release of SiO3. 2- Then switch to open circuit potential or slightly positive potential (+0.1~+0.3V) for 30-60s to suppress excessive dissolution; repeat the pulse cycle 5-15 times until the liquid phase SiO2 concentration reaches 0.08-0.15g / mL. S3. Electrochemical-induced crystallization: Add supplementary silicon source, such as silica sol or fumed silica, to the mixture after pulse potential regulation to achieve a total SiO2 / Al2O3 molar ratio of 0.4-0.7. Adjust the pH to 4.5-6.5, add TEA template agent, and crystallize at autogenous pressure and 150-180℃ for 24-72 hours. During crystallization, maintain intermittent pulse potential and apply a -0.4V reduction potential for 30 minutes every 6 hours to continuously replenish the Si species consumed during crystallization and prevent the formation of Si-deficient regions near the crystal nucleus. S4. Post-processing: After centrifugation, washing, and drying, the crystallized product is calcined at 550-600℃ for 4-6 hours to obtain a highly crystalline electrochemically activated kaolin-based SAPO-34 molecular sieve.

[0008] Furthermore, the electrochemical anodizing described in step S1 is assisted by an asymmetric alternating electric field: a low-frequency alternating component is superimposed on the basis of DC anodizing, with a frequency of 0.1-1Hz and an amplitude of 20-30% of the DC component, which promotes the reciprocating migration of ions between kaolin layers and accelerates the peeling of the layered structure. The peeling efficiency is 40-60% higher than that of pure DC anodizing.

[0009] Furthermore, the pulse potential program in step S2 employs adaptive feedback control: the concentration of Si in the liquid phase is monitored online by inductively coupled plasma atomic emission spectroscopy or the molybdenum blue colorimetric method. When the Si concentration is below 0.06 g / mL, a reduction pulse is automatically triggered. When the Si concentration is above 0.18 g / mL, the circuit is switched to an open-circuit potential or a positive limiting potential (+0.1~+0.3V vs. Ag / AgCl), thereby achieving dynamic matching between the Si release rate and the SAPO-34 crystallization consumption rate.

[0010] The second objective of this invention is achieved by the following technical solution: Includes: SAPO-34 nanocrystalline phase: particle size 40-100nm, crystallinity ≥90%, micropore volume 0.24-0.28cm³ / g; Functionalized kaolin nanosheets: 5-20 nm thick, rich in ≡Si-OH and ≡Al-OH groups on the surface, with a density of ≥3.5 groups / nm², serving as an epitaxial growth substrate for SAPO-34 nanocrystals; Interfacial chemical bonding region: SAPO-34 crystal nuclei are nucleated on the surface of kaolin nanosheets, and Al-O-Si covalent bonds are formed between the (001) facet of the crystal nucleus and the surface of the kaolin nanosheets. The interfacial bonding energy is 2-3 times higher than that of physical adsorption. In-situ self-assembled mesoporous channels: Kaolin nanosheets are stacked to form 2-10 nm interlayer mesopores with a mesopore volume of 0.08-0.15 cm³ / g, which serve as rapid diffusion channels connecting SAPO-34 micropores to the outer surface of the composite material.

[0011] The third objective of this invention is achieved by the following technical solution: The application of electrochemically activated kaolin-based SAPO-34 composite molecular sieve in methanol-to-olefins reaction, with a reaction temperature of 420-480℃, a pressure of 0.1-0.5MPa, and a methanol weight hourly space velocity of 1.5-4h-1.

[0012] Compared with the prior art, the beneficial effects of the present invention are as follows: This invention provides a method for preparing electrochemically activated kaolin-based SAPO-34 molecular sieves. (1) Electrochemical activation is carried out at room temperature, which reduces energy consumption by 60-80% compared with traditional high-temperature calcination. The degree of activation can be precisely controlled by current density and time, avoiding the densification of layered structure caused by high temperature of 750-900℃, preserving the complete macroporous framework and layered stacked structure, and providing a mechanical support basis for the catalyst; (2) Solve the problem of mismatch between silicon source concentration decay and crystallization: By dynamically controlling the release of Si through pulse potential program, the concentration of SiO2 in liquid phase is maintained in a stable window of 0.08-0.15 g / mL, which matches the crystallization consumption rate of SAPO-34, avoiding the formation of Si-deficient areas, and the crystallinity of the product reaches 94-98%, without AlPO4 or SAPO-18 impurity phases. (3) Solving the problems of large grain size and long diffusion path: The high active sites (≥3.5 sites / nm²) on the surface of activated kaolin nanosheets induce a 10-100-fold increase in heterogeneous nucleation density, resulting in the simultaneous formation of a large number of crystal nuclei; combined with pulsed silicon supply to maintain moderate supersaturation, a mild crystallization temperature (150-180℃) to reduce the growth rate, and interfacial Al-O-Si bond anchoring to limit grain expansion, SAPO-34 nanocrystals can be controllably grown to 40-100nm (thickness 30-50nm), instead of the 0.5-2μm large crystals of the traditional method; the diffusion path is shortened from the traditional 500-1000nm to ≤80nm, and the olefin residence time is reduced by >60%; (4) Kaolin nanosheets serve as both a carrier and a silicon source, forming a three-level continuous pore system of micropores, mesopores, and macropores, which shortens the diffusion path and reduces the carbon deposition rate. (5) Interfacial Al-O-Si chemical bonding enhances structural stability, and the catalyst compressive strength is ≥35 N·mm. -2 This meets the requirements of a fluidized bed. Detailed Implementation

[0013] The present invention will be further described below with reference to specific embodiments. It should be noted that, without conflict, the embodiments or technical features described below can be arbitrarily combined to form new embodiments.

[0014] Raw material source: Kaolin: Produced in Maoming, Guangxi, SiO2 46.3wt%, Al2O3 38.1wt%, Fe2O3 <0.8wt%, D 50 =3.2μm; Phosphoric acid: H3PO4 85wt%, analytical grade; Tetraethyl orthosilicate (TEOS): analytical grade, SiO2 content 28.4 wt%; Silica sol: 30wt% SiO2, particle size 7-12nm, pH=9.5; Triethylamine (TEA): Analytical grade, content ≥99%; Sodium hydroxide: analytical grade, content ≥96%.

[0015] Test method: X-ray diffraction (XRD): Rigaku MiniFlex 600, Cu Kα radiation, scan range 5-40°, step size 0.02°; Specific surface area and pore structure: Micromeritics ASAP2460, N2 adsorption-desorption method, micropore volume was calculated using the t-plot method, and mesopore volume was calculated using the BJH method; X-ray photoelectron spectroscopy (XPS): Thermo Scientific K-Alpha, Al Kα radiation; Inductively coupled plasma optical emission spectroscopy (ICP-OES): Perkin Elmer Optima 8000, for determining the concentrations of Si and Al in the liquid phase; Ammonia temperature-programmed desorption (NH3-TPD): Micromeritics Auto ChemII 2920, heating rate 10℃ / min, endpoint 600℃; Evaluation of methanol-to-olefins reaction: Fixed-bed reactor, inner diameter 10 mm, catalyst loading 2.0 g, reaction temperature 450 °C, methanol WHSV = 2 h⁻¹ -1 Nitrogen was used as the carrier gas, and the product was analyzed by online gas chromatography.

[0016] Example 1 This embodiment provides a method for preparing electrochemically activated kaolin-based SAPO-34 molecular sieves, which includes the following steps: S1. Electrochemical anodic oxidation stripping: 100g of kaolin powder was mixed with 20mL of 5wt% polyvinyl alcohol aqueous solution and pressed into a circular electrode with a diameter of 50mm and a thickness of 3mm. Using this electrode as the anode, a stainless steel sheet as the cathode, and 1.0M NaOH solution as the electrolyte, a constant current density of 20mA / cm² was applied. 2 Anodizing was performed for 60 min. During the process, the Al-O octahedral layers between the kaolin sheets underwent selective dissolution, resulting in the exfoliation of the layered structure. After treatment, the kaolin nanosheets in the suspension were collected, centrifuged and washed until neutral, and then dried for later use. XPS analysis showed that the density of ≡Si-OH and ≡Al-OH groups on the surface was 4.2 groups / nm. 2 Compared to the original kaolin (1.8 particles / nm) 2 (Increased by 133%).

[0017] S2. Pulse Potential Regulation of Silicon Release: 20g of kaolin nanosheets obtained in step S1 were transferred to a crystallization vessel with a three-electrode system. 150mL of deionized water, 18.5g of 85% phosphoric acid, and 25g of triethylamine were added. The working electrode was a kaolin nanosheet current collector, the counter electrode was a Pt sheet, and the reference electrode was Ag / AgCl. The pulse potential program was initiated: a reduction potential of -1.0V (vs. Ag / AgCl) was applied for 90s to promote the breaking of Si-O bonds and release of Si; the open-circuit potential was switched for 45s to suppress excessive dissolution. The pulse cycle was repeated 10 times. Online monitoring by ICP-OES showed that the concentration of SiO2 in the liquid phase gradually increased from 0.02g / mL to 0.12g / mL, and the concentration of Al2O3 was 0.08g / mL. S3. Electrochemical-induced crystallization: Add 14g of silica sol to the above mixture to achieve a total SiO2 / Al2O3 molar ratio of 0.55, and adjust the pH to 5.2 with dilute phosphoric acid. Seal the crystallization vessel and crystallize at autogenous pressure and 170℃ for 48h. During crystallization, apply a reduction potential of -0.4V for 30min every 6h to replenish the Si species consumed during crystallization. After crystallization, the solid product in the vessel is centrifuged and washed until the conductivity is <200μS / cm, and then dried at 120℃ for 12h. S4. Calcination and activation: The dried product was heated to 550℃ at 2℃ / min and calcined for 5h to remove the template agent, thus obtaining an electrochemically activated kaolin-based SAPO-34 composite molecular sieve, denoted as sample A.

[0018] XRD characterization results: SAPO-34 characteristic diffraction peaks appeared at 2θ = 9.5°, 13.2°, 16.2°, 20.8°, and 25.9°, with no AlPO4 or SAPO-18 impurity phase peaks, and a crystallinity of 94%; BET (Table 1): total specific surface area 685 m². 2 / g, micropore volume 0.26cm³ 3 / g, mesopore volume 0.14cm 3 / g, total pore volume 0.40cm³ 3 / g; XPS (Table 2): Si 2p binding energy is 102.8 eV, which is 0.3 eV higher than that of pure SAPO-34 (102.5 eV), confirming Al-O-Si interfacial bonding.

[0019] MTO reaction evaluation: In a fixed-bed reactor, at 450℃ and WHSV=2h -1 Under the given conditions, the catalytic performance of sample A is shown in Table 3. The methanol conversion rate is >99%, the maintenance time is 195 h, the ethylene + propylene selectivity is 83.2% on average, and the carbon deposition rate is 5.8 wt% / 100 h.

[0020] Example 2 Preparation of SAPO-34 molecular sieves by asymmetric alternating electric field assisted anodic oxidation S1, Asymmetric AC electric field assisted anodizing The kaolin electrode was prepared in the same manner as in Example 1. Using 1.0 M NaOH as the electrolyte, an AC component with a frequency of 0.5 Hz and an amplitude of 25% of the DC component was superimposed on a constant DC current density of 30 mA / cm², for a total processing time of 45 min. The introduction of the AC component promoted the interlayer Na+ in the kaolin. + The repeated migration accelerates interlayer exfoliation. The resulting kaolin nanosheets have a thickness of 5-12 nm, which is thinner than in Example 1, with a radial dimension of 200-500 nm, and the yield is 55% higher than that of pure DC.

[0021] Steps S2-S4: Same as in Example 1, except the pulse potential parameters are adjusted as follows: reduction potential -0.9V, duration 80s; open circuit potential duration 40s; pulse cycle repeated 12 times. The final concentration of liquid-phase SiO2 is 0.10g / mL. Crystallization conditions: SiO2 / Al2O3 molar ratio 0.60, pH=5.5, crystallization at 175℃ for 42h to obtain sample B.

[0022] Characterization results: XRD: Crystallinity 96%, no impurities; BET (Table 1): Total specific surface area 712m² 2 / g, micropore volume 0.27cm³ 3 / g, mesopore volume 0.16cm 3 / g, total pore volume 0.43cm³ 3 / g; TEM: SAPO-34 grain size 40-70nm, thickness approximately 35nm; Compressive strength: 38 N·mm -2 .

[0023] MTO reaction evaluation (Table 3): Methanol conversion >99%, hold-up time 210 h, ethylene + propylene selectivity 84.5%, carbon deposition rate 5.2 wt% / 100 h. Performance was further improved compared to Example 1, attributed to the thinner nanosheets providing more mesoporous channels and active sites.

[0024] Example 3 Preparation of SAPO-34 molecular sieves by adaptive feedback control of pulse potential S1, Electrochemical anodic oxidation stripping Same as Example 1, current density 25mA / cm², processing time 55min.

[0025] S2, Adaptive feedback control pulse potential The crystallization reactor is equipped with an ICP-OES online monitoring system, which automatically samples and analyzes the Si concentration in the liquid phase every 5 minutes. The pulse potential program is set as follows: When [SiO2] < 0.06 g / mL, a reduction potential of -1.1 V is automatically triggered, lasting for 120 s; When [SiO2] > 0.16 g / mL, it automatically switches to a passivation potential of +0.2 V for 60 s. When 0.06 g / mL ≤ [SiO2] ≤ 0.16 g / mL, the open circuit potential is maintained.

[0026] The entire regulation process lasted 90 minutes, during which the concentration of SiO2 in the liquid phase remained stable within the range of 0.10-0.13 g / mL with fluctuations of <±8%, a significant improvement compared to the timed pulse mode in Example 1 (fluctuations ±25%). The concentration of Al2O3 remained stable within the range of 0.07-0.09 g / mL.

[0027] S3. Electrochemically induced crystallization: Silica sol was added to adjust the total SiO2 / Al2O3 ratio to 0.50, pH to 5.0, and crystallization was carried out at 165℃ for 54 hours. The adaptive pulse mode was activated every 6 hours, automatically adjusting the potential and duration based on the real-time Si concentration to obtain sample C.

[0028] Characterization results: XRD: Crystallinity 98%, the highest among the three examples, with no impurities; BET (Table 1): Total specific surface area 668 m² / g, micropore volume 0.27 cm³ / g, mesopore volume 0.13 cm³ / g, total pore volume 0.40 cm³ / g; SEM / TEM: SAPO-34 has the narrowest grain size distribution (50-70nm) and the best uniformity; XPS: Si 2p binding energy shifted by 0.35 eV, with the strongest interfacial bonding; NH3-TPD: Total acidity 1.12 mmol / g, with the most uniform acid strength distribution.

[0029] MTO reaction evaluation (Table 3): The methanol conversion rate was >99%, with a duration of 225 hours, the longest among the three examples; the ethylene + propylene selectivity was 85.1%; and the carbon deposition rate was 4.9 wt% / 100 hours, the lowest among the three examples. Adaptive feedback control achieved optimal matching between Si release and crystallization consumption, resulting in the best product performance.

[0030] Comparative Example 1 SAPO-34 prepared by traditional high-temperature calcination activation method Kaolin was calcined at 750℃ for 4 hours to transform into metakaolin. 20g of metakaolin, 18.5g of phosphoric acid, 25g of triethylamine, 14g of silica sol, and 150mL of deionized water were mixed to adjust the SiO2 / Al2O3 ratio to 0.55 and the pH to 5.2. The mixture was then hydrothermally crystallized at 200℃ for 48 hours and calcined at 550℃ for 5 hours to obtain sample D.

[0031] Characterization results: XRD: crystallinity 78%, with obvious AlPO4 impurity phase peaks (2θ=21.5°, 23.2°); BET (Table 1): Total specific surface area 485m² 2 / g, micropore volume 0.19cm³ 3 / g, mesopore volume 0.06cm³ 3 / g MTO reaction evaluation (Table 3): The methanol conversion rate was maintained at >99% for only 85 hours, the ethylene + propylene selectivity was 76.3%, and the coking rate was 11.5 wt% / 100h. High-temperature calcination caused partial sintering of kaolin, resulting in slow and uneven Si release, more impurity phase formation, and significantly inferior catalytic performance compared to the example.

[0032] Comparative Example 2 Electrochemical activation method without pulse potential control Step S1 is the same as in Example 1. In step S2, after mixing kaolin nanosheets with phosphoric acid and triethylamine, silica sol is directly added without applying a pulse potential. The SiO2 / Al2O3 ratio is 0.55, pH is 5.2, and crystallization is carried out at 170℃ for 48 hours. Sample E is obtained.

[0033] Characterization results: XRD: crystallinity 82%, with weak SAPO-18 impurity phase peaks (2θ=9.2°, 20.4°); BET (Table 1): total specific surface area 542 m² / g, micropore volume 0.21 cm³ / g; SEM: SAPO-34 grain size is uneven (60-150nm), with grain aggregation in some areas.

[0034] MTO reaction evaluation (Table 3): Methanol conversion rate >99%, maintenance time 110h, ethylene + propylene selectivity 78.6%. The lack of pulse control resulted in excessively rapid initial Si release and insufficient later release, leading to uneven crystallization. The performance was between that of Example 1 and Comparative Example 1.

[0035] Summary of experimental data Table 1 Sample Hole Structure Parameters Table 2 Elemental Analysis of XPS Surface Table 3 Catalytic performance of MTO reaction in conclusion This invention achieves mild and efficient activation of kaolin through electrochemical anodic oxidation, combined with precise control of Si release kinetics via pulsed potential programming. This solves key technical problems of traditional methods, such as harsh activation conditions, low Si-Al utilization, and uneven product crystallinity. The sample in the examples exhibits excellent catalytic performance in the methanol-to-olefins reaction: diene selectivity ≥83%, catalytic lifetime ≥195h, coking rate ≤5.8wt% / 100h, and mechanical strength meeting fluidized bed requirements, significantly outperforming traditional high-temperature calcination methods and pulseless electrochemical methods.

[0036] The above embodiments are merely preferred embodiments of the present invention and should not be construed as limiting the scope of protection of the present invention. Any non-substantial changes and substitutions made by those skilled in the art based on the present invention shall fall within the scope of protection claimed by the present invention.

Claims

1. A method for preparing electrochemically activated kaolin-based SAPO-34 molecular sieves, characterized in that, The steps are as follows: S1. Electrochemical anodic oxidation exfoliation: Kaolin powder is pressed into electrode sheets as the anode, and anodic oxidation is performed for 30-120 min at a constant current density of 10-50 mA / cm² using 0.5-2 M NaOH or KOH solution as the electrolyte. During the anodic oxidation process, the Al-O octahedral layers between the kaolin sheets undergo selective dissolution, and the layered structure is exfoliated to form ultrathin kaolin nanosheets with a thickness of 5-20 nm and a radial dimension of 200-800 nm. At the same time, abundant ≡Si-O⁻ and ≡Al-O⁻ active sites are generated on the surface. S2. Pulse Potential Controlled Silicon Release: The kaolin nanosheets treated in step S1 are transferred to a crystallization reactor, and deionized water, phosphorus source, and template agent are added. A three-electrode system is used, in which the kaolin nanosheets are the working electrode, Pt is the counter electrode, and Ag / AgCl is the reference electrode. The release of Si is controlled by a pulse potential program: a reduction potential of -0.8 to -1.2V (vs. Ag / AgCl) is first applied for 60-120s to promote the breaking of Si-O bonds on the surface and release of SiO3. 2- Then switch to open circuit potential or slightly positive potential (+0.1~+0.3V) for 30-60s to suppress excessive dissolution; repeat the pulse cycle 5-15 times until the liquid phase SiO2 concentration reaches 0.08-0.15g / mL. S3. Electrochemical-induced crystallization: Add supplementary silicon source, such as silica sol or fumed silica, to the mixture after pulse potential regulation to achieve a total SiO2 / Al2O3 molar ratio of 0.4-0.

7. Adjust the pH to 4.5-6.5, add TEA template agent, and crystallize at autogenous pressure and 150-180℃ for 24-72 hours. During crystallization, maintain intermittent pulse potential and apply a -0.4V reduction potential for 30 minutes every 6 hours to continuously replenish the Si species consumed during crystallization and prevent the formation of Si-deficient regions near the crystal nucleus. S4. Post-processing: After centrifugation, washing, and drying, the crystallized product is calcined at 550-600℃ for 4-6 hours to obtain a highly crystalline electrochemically activated kaolin-based SAPO-34 molecular sieve.

2. The method for preparing an electrochemically activated kaolin-based SAPO-34 molecular sieve according to claim 1, characterized in that, The electrochemical anodizing described in step S1 is assisted by an asymmetric alternating electric field: a low-frequency alternating component is superimposed on the DC anodizing, with a frequency of 0.1-1Hz and an amplitude of 20-30% of the DC component, which promotes the reciprocating migration of ions between kaolin layers and accelerates the peeling of the layered structure. The peeling efficiency is 40-60% higher than that of pure DC anodizing.

3. The method for preparing an electrochemically activated kaolin-based SAPO-34 molecular sieve according to claim 1, characterized in that, The pulse potential program in step S2 adopts adaptive feedback control: the concentration of Si in the liquid phase is monitored online by inductively coupled plasma emission spectroscopy or the silicon molybdenum blue colorimetric method. When the Si concentration is lower than 0.06 g / mL, the reduction pulse is automatically triggered. When the Si concentration is higher than 0.18 g / mL, the program switches to an open circuit potential or a positive limiting potential (+0.1~+0.3V vs. Ag / AgCl) to achieve dynamic matching between the Si release rate and the SAPO-34 crystallization consumption rate.

4. An electrochemically activated kaolin-based SAPO-34 composite molecular sieve, characterized in that, include: SAPO-34 nanocrystalline phase: particle size 40-100nm, crystallinity ≥90%, micropore volume 0.24-0.28cm³ / g; functionalized kaolin nanosheets: thickness 5-20nm, surface rich in ≡Si-OH and ≡Al-OH groups, density ≥3.5 groups / nm², used as epitaxial growth substrate for SAPO-34 nanocrystals; Interfacial chemical bonding region: SAPO-34 crystal nuclei are nucleated on the surface of kaolin nanosheets, and Al-O-Si covalent bonds are formed between the (001) facet of the crystal nucleus and the surface of the kaolin nanosheets. The interfacial bonding energy is 2-3 times higher than that of physical adsorption. In-situ self-assembled mesoporous channels: Kaolin nanosheets are stacked to form 2-10 nm interlayer mesopores with a mesopore volume of 0.08-0.15 cm³ / g, which serve as rapid diffusion channels connecting SAPO-34 micropores to the outer surface of the composite material.

5. The application of the electrochemically activated kaolin-based SAPO-34 composite molecular sieve according to claim 4 in the methanol-to-olefins reaction, characterized in that, The reaction temperature was 420-480℃, the pressure was 0.1-0.5 MPa, and the methanol weight hourly space velocity was 1.5-4 h⁻¹. -1 .